Phytogeography of the genus Microcos L. (Malvaceae, Grewioidae) in Africa - Czarnecka , Elżbieta; Wiland-Szymańska, Justyna; Gawrońska, Kinga (Biodiversity: Research and Conservation, 2006)
The aim of this study was to determine the number of species of the genus Microcos in African countries. Species of this genus are confined to wet equatorial forests and mountain forests. Therefore a centre of diversity of the genus Microcos in Africa is found in the Democratic Republic of the Congo. Areas of lower species richness are Cameroon, Nigeria, Tanzania and Uganda. Several types of distribution patterns of species of Microcos were distinguished.